MODEL PEMBERDAYAAN PETANI BAWANG MERAH MELALUI SISTEM BANK BENIH UNTUK PENINGKATAN KAPASITAS PETANI (Suatu Kasus Pada Kelompok Tani Mekar Jaya Desa Tonjong) - Aliudin, Aliudin; Wibowo, Aris Supriyo; Sariyoga , Setiawan; Meutia, Meutia (CV. Era Digital Nusantara, 2022)
Farmers in shallots in central locations in Serang Regency are faced with seed problems. The problem of the availability of shallot seeds hampers the planting schedule so that shallot production decreases. One of the solutions offered in this activity is to provide independent seeds provided directly by farmers through seed banks. This activity aims to create a model for the empowerment of shallot farmers with a seed bank system. The methods used in this activity are descriptive and observational methods. The method of observation was carried out directly on farmer groups using a census sampling technique of 65 members of farmer groups. The criteria used in the sampling technique with the limitation that the farmers who will be sampled are farmers who grow shallots for seed purposes. The results of the activity show that the appropriate model for empowering farmers with the shallot seed bank system is the Natura Revolving Seed Bank Model. The in-kind rolling seed model is considered to be in accordance with the considerations because this model has the resilience to roll and its sustainability is guaranteed.